PENGARUH MODEL DISCOVERY LEARNING PADA MATERI PKN TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V - Renaldi, M.; Syamsuyurnita, Syamsuyurnita; Saragih, Mandra; Nasution, Ismail Saleh (STKIP PGRI Situbondo, 2024)
The purpose of this research is to determine the effect of the Discovery learning model in Civics material on the critical thinking abilities of fifth grade students. The research uses quantitative methods with the discovery learning model. The Quantitative method is research that uses a lot of numbers, starting from the data collection process to its interpretation. This research was carried out in class V of the Gombak Selangor Malaysia DICTIONARY Learning Studio. using a population of 8 students who were also used as samples. This sampling technique uses a saturated sampling technique, where this technique makes the entire population the sample. The results of data analysis after the t-test data on pretest and posttest scores showed that from the 8 samples obtained an average score of 76.60 with a standard deviation of 10.784 and the average posttest score was 87.25 with a standard deviation of 6.798. After testing the hypothesis the tailed sig value is 0.000 < 0.05, a decision can be made that Ha is accepted. In other words, the discovery learning learning model in PKN learning has an influence on class V students of the KAMUS Study Studio, North Gombak, Selangor, Malaysia.